Effects of intra- and inter-team dynamics on organisational learning: role of knowledge-sharing capability. Issue 1 (1st February 2017) - Presbitero, Alfred; Roxas, Banjo; Chadee, Doren
Abstract: This research investigates the moderating role of knowledge-sharing capability on the effects of team dynamics on organisational learning by decomposing team dynamics into two types, namely, intra-team and inter-team dynamics. Using structural equation modelling techniques and data from a large-scale survey of employees in Australia, it is shown that inter-team dynamics has a larger direct effect on organisational learning compared with intra-team dynamics. However, when taking the moderating effects of knowledge-sharing capability into consideration, intra-team dynamics contribute more to organisational learning. The findings suggest that knowledge-sharing capability is more critical within teams rather than between teams in enhancing organisational learning. The implications of these findings for knowledge management research and practice are fully discussed.